Involvement of microbiota and short-chain fatty acids on non-alcoholic steatohepatitis when induced by feeding a hypercaloric diet rich in saturated fat and fructose - Iñaki Milton-Laskibar; Laura Judith Marcos-Zambrano; Saioa Gómez-Zorita; Enrique Carrillo de Santa Pau; Alfredo Fernández-Quintela; Jose Alfredo Martínez; María Puy Portillo (Gut Microbiome, 2022)
Consumption of high-energy-yielding diets, rich in fructose and lipids, is a factor contributing to the current increase in non-alcoholic fatty liver disease prevalence. Gut microbiota composition and short-chain fatty acids (SCFAs) production alterations derived from unhealthy diets are considered putative underlying mechanisms. This study aimed to determine relationships between changes in gut microbiota composition and SCFA levels by comparing rats featuring diet-induced steatohepatitis with control counterparts fed a standard diet. A high-fat high-fructose (HFHF) feeding induced higher body, liver and mesenteric adipose tissue weights, increased liver triglyceride content and serum transaminase, glucose, non-HDL-c and MCP-1 levels. Greater liver malondialdehyde levels and glutathione peroxidase activity were also observed after feeding the hypercaloric diet. Regarding gut microbiota composition, a lowered diversity and increased abundances of bacteria from the Clostridium sensu stricto 1, Blautia, Eubacterium coprostanoligenes group, Flavonifractor, and UBA1819 genera were found in rats featuring diet-induced steatohepatitis, as well as higher isobutyric, valeric and isovaleric acids concentrations. These results suggest that hepatic alterations produced by a hypercaloric HFHF diet may be related to changes in overall gut microbiota composition and abundance of specific bacteria. The shift in SCFA levels produced by this unbalanced diet cannot be discarded as potential mediators of the reported hepatic and metabolic alterations.